Investigations on the wire EDM characteristics of Al matrix composite using TOPSIS method. (2023) - Senthamarai, K.; Deepak, D.; Saravanan, H.; Gopikrishnan, C.; Alagarsamy, S.V.; Chanakyan, C.
Abstract: This study deals with wire electrical discharge machining (WEDM) of alumina (Al2 O3 ) reinforced AA6063 matrix composite using a brass wire electrode to analyze the two important characteristics concerning material removal rate (MRR) and surface roughness (Ra). Nine combinations of experimental runs are performed by taking three input parameters (peak current (Ip ), pulse-on time (Ton ) and pulse-off time (Toff )) based on Taguchi's design of experiments. In addition, Technique for order preference by similarity to ideal solution is employed for multi-response optimization. Thereafter, analysis of variance (ANOVA) is employed to determine the influence of parameters on responses. From TOPSIS results identified that the optimal parameters for obtain the higher MRR and lower Ra are 'Ip ' of 20A, 'Ton ' of 100 µs and 'Toff ' of 30 µs, respectively. ANOVA result revealed that 'Ton ' has the main significant factor (42.40 %) in enhancement of MRR and deprivation of Ra, followed by 'Ip ' (28.53 %) and 'Toff ' (16.63 %), respectively.